The evolution ofpolitical and legal thoughtin poetryzhyrauduring thestrengtheningof the Kazakh Khanate (Journal of actual problems of jurisprudence, 2018)
The article discusses the evolution ofpolitical and legal thoughtin poetryzhyrauduringstrengthening of the Kazakh Khanate. Strengthening Khanateled to a conflictof interest between thetraditional institutions of state power. Competition of ideason buildinga strong stateandunionbetweenthe people of the khan’spower andzhyrauopenednew avenues for the development of political and legal thought.Key words: zhyraupoetry, political and legalthought, the idea of unity, political repression.